(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The growth and sustainability of Small and Medium Enterprises (SMEs) are crucial for the economic development of any nation. The government of Ghana, in recognition of this, established the Ghana Enterprises Agency to promote the growth and development of Micro and Small Enterprises (MSEs). This study aimed to identify the core attributes and areas of specialization of Small and Medium Textile Enterprises (SMTEs) in Ghana to provide the necessary support, identify employment opportunities, and mobilize the needed revenue for development. A descriptive research design was used for the study, with a sample size of 273 out of 300 questionnaires distributed to small and medium textile manufacturers in Greater Accra, Ashanti, Northern, and Western regions. The study employed multi-stage sampling techniques involving convenient, purposive, and stratified sampling procedures. The findings revealed that Greater Accra and the Ashanti region have the highest population of SMTEs in Ghana. The average annual earning of SMTEs in Ghana was around Gh¢18,000, which suggests more room for improvement. The study recommends that the government must provide valuable resources, particularly financial and strategic support, for the development of the private sector, particularly SMEs. The study also identified that the textile industry has significant potential for job creation and revenue generation, particularly in the face of rising youth unemployment rates in Ghana. Therefore, the government should promote investment in the textile sector, particularly for SMTEs, through policies that prioritize infrastructural development, access to finance, and targeted training programs. Overall, this study highlights the importance of supporting SMEs, particularly in the textile industry, as a vital means of promoting economic growth and development in Ghana.